PENGEMBANGAN VIDEO PEMBELAJARAN ANIMASI BERBASIS ANIMAKER MATERI GARIS DAN SUDUT UNTUK MENINGKATKAN MINAT BELAJAR SISWA SMPN 1 GEGER DI MASA PANDEMI COVID-19 - Vera Dewi Susanti; Alma Damayanti (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
Education that is carried out remotely results in a decrease in students' interest in learning. This study aims to develop and produce learning video media that can be used remotely. Media development uses a 4D development model to the third stage, namely defining, planning, and developing. The results of the research are 1) Animaker-based Animated Learning Video Media is declared quite valid with an average assessment result by the validator of 79.52%. 2) Animaker-Based Animation Learning Video Media is declared practical based on the average value obtained from the student response questionnaire sheet of 89.26%. 3) Animaker-based Animation Learning Video Media is declared to be effective in learning with the average results obtained from student learning outcomes tests of 84.95%. mathematics on Lines and Angles.